VISUAL ANALYTICS AND PREDICTIVE MODELLING FOR INTERPRETING FINANCIAL NARRATIVES IN DIGITAL MEDIA - Parashar, Mukesh; Girdhar, Ram; Kulkarni, Swarali Shailesh; Kaur, Simrandeep; Pande, Mukul; Ramteke, Neha (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The given study introduces a visual analytic and predictive modelling concept of interpreting financial narratives in digital media, which holds the problem of volatility-inducing sentiment, narrative bias, and informational overload of news, social sites, and corporate disclosures. The aim is to make a systematic comprehension of the impact of visual signals, linguistic structuring and time dynamics on market-relevant narratives and expectations. The suggested approach will combine multimodal visual analytics, natural language processing, and time-series prediction. Visual modules process charts, infographics, thumbnails and video frame trends, extract emphasis of trends, scale distortion, color semantics as well as attention cues whereas language models identify sentiment polarity, stance, uncertainty and causal framing. Such properties are combined on the basis of transformer-based schemata and matched with market indicators to acquire narrative and market correlations. Predictive components are models using probabilistic prediction to estimate the volatility and directional risk of short horizon in conditioned directions using narrative signals. On massive financial media datasets, assessments show a reality that more accurately extracts narratives and predicts risks with gains of up to 16 and 14 per cent on sentiment -return correspondence and false volatility alarms respectively over text-only controls. The interactive visual dashboards present elucidative insights, indicating persuasive visuals, words, and time changes, which propel the predictions. The results reveal that visual analytics, when paired together with predictive modelling, can create a robust transparent method of decoding financial stories that will in turn aid analysts, regulators and investors to make decisions in time and also make informed choices about literacy on media in the rapidly changing digital information ecosystems. It also allows cross-platform comparison, stress testing, and early warning in the face of uncertainty to the stakeholders worldwide.